Digoxin and Risk of Death in Adults With Atrial Fibrillation: The ATRIA-CVRN Study. (February 2015) - Freeman, James V.; Reynolds, Kristi; Fang, Margaret; Udaltsova, Natalia; Steimle, Anthony; Pomernacki, Niela K.; Borowsky, Leila H.; Harrison, Teresa N.; Singer, Daniel E.; Go, Alan S.
Abstract : Background—: Digoxin remains commonly used for rate control in atrial fibrillation, but limited data exist supporting this practice and some studies have shown an association with adverse outcomes. We examined the independent association between digoxin and risks of death and hospitalization in adults with incident atrial fibrillation and no heart failure. Methods and Results—: We performed a retrospective cohort study of 14 787 age, sex, and high-dimensional propensity score-matched adults with incident atrial fibrillation and no previous heart failure or digoxin use in the AnTicoagulation and Risk factors In Atrial fibrillation-Cardiovascular Research Network (ATRIA-CVRN) study within Kaiser Permanente Northern and Southern California. We examined the independent association between newly initiated digoxin and the risks of death and hospitalization using extended Cox regression. During a median 1.17 (interquartile range, 0.49–1.97) years of follow-up among matched patients with atrial fibrillation, incident digoxin use was associated with higher rates of death (8.3 versus 4.9 per 100 person-years; P <0.001) and hospitalization (60.1 versus 37.2 per 100 person-years; P <0.001). Incident digoxin use was independently associated with a 71% higher risk of death (hazard ratio, 1.71; 95% confidence interval, 1.52–1.93) and a 63% higher risk of hospitalization (hazard ratio, 1.63; 95% confidence interval, 1.56–1.71). Results were consistent in subgroups of age and sex and when using intent-to-treat or on-treatment analytic approaches. Conclusions—: In adults with atrial fibrillation, digoxin use was independently associated with higher risks of death and hospitalization. Given other available rate control options, digoxin should be used with caution in the management of atrial fibrillation. Abstract : Supplemental Digital Content is available in the text.